A Model of Educational Inspection for the Improvement of Quality and Equity, between Governance and Autonomy of Schools - Cuadrado Muñoz, Francisco J. (Avances en Supervisión Educativa, 2024)
Improving the quality and equity of education continues to be the fundamental task of the education system under the influence of international organizations, in a world that is constantly changing, with great present and future challenges. There is a growing interest in educational inspection in our century at the international level as a consequence of the changes in educational governance in the last decades and, especially, with the impulse of autonomy with accountability in schools and external testing. Educational inspection needs to reposition itself with an appropriate and relevant role aligned with these changes also in Spain, in a complete inspection model of comprehensive external evaluation of educational centres, which is a common object of interest and performance in most of the European educational inspections, as part of accountability.